The syntax of generics and the absence of generic articles - Husband, EM (Linguistic Society of America, 2022)
Cross-linguistically, no language has a dedicated generic article. To address why this is, I decompose GEN into its quantificational and modal components and locate them inside nominal structure. Adopting an event licensing analysis of pre- and post-verbal bare subjects in Modern Hebrew, I use the restriction of pre-verbal bare subjects to generic interpretations and unacceptability of pre-verbal bare singulars to argue that the quantificational component of GEN is best analyzed as a D-quantifier. Evidence from adnominal conditionals further identifies a modal source for GEN within the nominal, which I suggest is adjectival and derived from a reduced relative clause source. I propose that the formation of generic articles is blocked by the non-local (e.g. non-spanning) relationship between these quantificational and modal components.